Internet connectivity disruption in Iran (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Iran. Data sourced from IODA.
Network Disruption Incident ID: IR-2026-0612. Severity: critical. Confidence: 67%